An investigation into the effects of band gap and doping concentration on Cu(In,Ga)Se(2) solar cell efficiency - Asaduzzaman, Md. (Springerplus, 2016)
A simulation study of a Cu(In(1 − x)Ga(x))Se(2) (CIGS) thin film solar cell has been carried out with maximum efficiency of 24.27 % (V(oc) = 0.856 V, J(sc) = 33.09 mA/cm(2) and FF = 85.73 %). This optimized efficiency is obtained by determining the optimum band gap of the absorber and varying the doping concentration of constituent layers. The Ga content denoted by x = Ga/(In + Ga) is selected as 0.35 which provides the optimum band gap of absorber layer as 1.21 eV. Theoretically, the effects of Ga fraction “x” on CIGS absorber band gap are investigated and to avoid the lattice mismatch effect, the efficiency measurements due to the CIGS band gaps >1.21 eV have not come to the consideration. A one-dimensional simulator ADEPT/F 2.1 has been used to analyze the fabricated device parameters and hence to calculate open circuit voltage, short circuit current, fill factor and efficiency.